Culturally responsive teaching : - Irvine, Jacqueline Jordan (McGraw-Hill, 2001)
How do I plan lessons for today;s diverse classrooms? This book helps pre-service teachers answer this question and learn to create and use such lessons in their classrooms. It is the first book to provide well-developed content-specific lesson plans that reflect cultural diversity in the United States. Rather than taking the traditional foundations-oriented, culture and history approach, this text translates that cultural and historical knowledge of specific minority groups into examples for instructional use. The text features entire field-tested units for elementary and middle grades in four content areas, language arts, mathematics, science, and social studies. For example, in the language arts unit, "Stories, Stories, Stories," students tell, write, and read stories that build on their cultural background and experiences. The math unit explores informal geometry in the patterns of Navajo rugs, African textiles, and Mexican pottery. The science unit connects weather experiences to cultural folk myths and sayings. The social studies unit examines changing requirements for voting in the USA. The text can be used as a supplement for general or elementary methods, student field experience, or multicultural education, or as a main text in practice-oriented multicultural education and multicultural curriculum courses.